Child-to-parent abuse by late teens and young adults: risks and interventions - Silos, Natasha (2020)
Background: Child-to-parent abuse (CPA) is an area of family violence that has remained relatively under researched. Our current understanding of the risk factors and interventions for this type of abuse, particularly within the United Kingdom (U.K.), is limited.